Antiquity Reused. Antique Engraved Gems on Byzantine Rings - Albani, Jenny (Actual Problems of Theory and History of Art, 2015)
It is nowadays generally accepted that the Byzantines were familiar with the art of the antiquity. In this context antique gemstones, cameos and intaglios, were incorporated in mediaeval jewellery, especially in rings. How did the Byzantines “reuse antiquity” in relation to their rings, these precious objects of prestige or personal adornment? Did they keep their original meaning or were they affected by Christian faith? Can we speculate on the identity of these rings’ owners? These are the questions which the author of the paper tries to deal with.
Keywords: Reuse; antiquity; Roman intaglios; Byzantine rings; inscriptions; mythological motifs; piety; amulets; Western influence